EVOLUSI KOMPUTER, KINERJA KOMPUTER DAN INTERCONNECTION NETWORKS DALAM PERKEMBANGAN DUNIA TEKNOLOGI INFORMATIKA - Junior, Henrico (Universitas Dirgantara Marsekal Suryadarma, 2016)
Informatika Engineering Department should be able to make plans in accordance with the Program in accordance with the wish to make. logic systematically created a very complex logical thinking is required, whereas if the program that we make must tratur and directed, it is quite a Progremer that make the program shall have a mathematical logic. In addition to thinking of efficient human resources, as a program must also determine what logical programming language that is suitable for use or do not even need to use a programming language, because it uses a programming language that requires great thought just to make simple and will not even static efficiency of In terms of the program.